Negative symptoms in schizophrenia: a study in a large clinical sample of patients using a novel automated method. Issue 9 (7th September 2015) - Patel, Rashmi; Jayatilleke, Nishamali; Broadbent, Matthew; Chang, Chin-Kuo; Foskett, Nadia; Gorrell, Genevieve; Hayes, Richard D; Jackson, Richard; Johnston, Caroline; Shetty, Hitesh; Roberts, Angus; McGuire, Philip; et al.
Abstract : Objectives: To identify negative symptoms in the clinical records of a large sample of patients with schizophrenia using natural language processing and assess their relationship with clinical outcomes. Design: Observational study using an anonymised electronic health record case register. Setting: South London and Maudsley NHS Trust (SLaM), a large provider of inpatient and community mental healthcare in the UK. Participants: 7678 patients with schizophrenia receiving care during 2011. Main outcome measures: Hospital admission, readmission and duration of admission. Results: 10 different negative symptoms were ascertained with precision statistics above 0.80. 41% of patients had 2 or more negative symptoms. Negative symptoms were associated with younger age, male gender and single marital status, and with increased likelihood of hospital admission (OR 1.24, 95% CI 1.10 to 1.39), longer duration of admission (β-coefficient 20.5 days, 7.6–33.5), and increased likelihood of readmission following discharge (OR 1.58, 1.28 to 1.95). Conclusions: Negative symptoms were common and associated with adverse clinical outcomes, consistent with evidence that these symptoms account for much of the disability associated with schizophrenia. Natural language processing provides a means of conducting research in large representative samples of patients, using data recorded during routine clinical practice.